Empowerment of Muhammadiyah Guidance Studio Students in Kuala Lumpur as Little Nurse Cadres - Agustini, Tutik; Yusriani, Yusriani; Burhanuddin, Nurfardiansyah (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2025)
Elementary schools serve as learning centers but are also prone to becoming sites for disease transmission if not properly managed. Data from the Makassar City Health Office in 2019 revealed high prevalence rates of diarrhea (50.89%), dermatitis (41.50%), and intestinal worm infections (56.80%) among elementary school-aged children, primarily due to poor personal and environmental hygiene. Similar health issues were observed among students in a mentoring center, where Clean and Healthy Living Behavior (CHLB) practices, as well as knowledge and skills in basic healthcare services, remained low.To address these issues, the establishment and training of young health cadres (PERCIL) were implemented at an elementary level in Madrasah Ibtidaiyah, located at 30 Wisma Sabarudin, Kuala Lumpur, Malaysia. The methods included literature studies, lectures, discussions, demonstrations, role-playing, and mentoring, with evaluation conducted using pre- and post-tests and skill checklists.The program results showed significant improvements in students’ knowledge, attitudes, and practices related to CHLB and their ability to provide basic healthcare services. Outputs included the formation of competent PERCIL cadres capable of disseminating health information and implementing CHLB concepts, publication in the ABDIMASNU Journal, dissemination in mass and online media, and an official service report. This program aims to create a healthy and productive group of children as a model for health interventions in other communities.